Implementation of Discovery Learning Model to Increase Student Interest and Learning Outcomes - Sulastri, Eni; Hidayat, Saleh; Saputri, Wulandari (research, training and philanthropy institution Natural Aceh, 2024)
This research aims to increase student interest and improve learning outcomes using the discovery learning model. This research uses the Action Research method. This research method starts with the planning, action implementation, observation, and reflection stages. Data Collection Techniques and Tools This research uses tests and observations. This class action was carried out at SMAN 1 Sungai Menang to determine students' interests and learning outcomes regarding applying the discovery learning model. This research shows an increase in interest, namely from 70.36% to 84% and student learning outcomes from the first and second cycles, namely from 25.92% to 85.17%. This increase is visible after implementing the discovery learning model, which can improve students' interests and learning outcomes. This research is implemented in two cycles; in the first cycle stage, the teacher provides a stimulus for students to identify and respond to problems and encourages students' critical thinking. In the second cycle, the teacher raises enthusiasm for learning by increasing students' interest in searching for related information and changing learning methods to make them more fun and interactive, such as through discussion activities that increase students' self-confidence and knowledge.